MODERN ASPECTS OF COAGULOPATHY DEVELOPMENT IN PATIENTS WITH COVID-19 INFECTION: LITERATURE REVIEW - M.O. Dudchenko; S.М. Zaiets; R.A. Prykhidko (Проблеми екології та медицини)
This review summarizes current knowledge about coagulation disorders associated with COVID-19 infection. Despite a significant amount of research, it is currently unclear whether COVID-19 is the direct cause of coagulopathic disorders or they occur as the infectious process progresses. Different authors have proposed several pathogenetic mechanisms for the development of coagulopathy in this disease. However, the most important is the release of a large number of cytokines that provoke interstitial inflammation, endothelial damage and activation of coagulation, in the pathogenesis of which the tissue factor plays a key role. Hyperinflammatory reactions lead to tissue damage, disruption of the endothelial barrier and uncontrolled activation of coagulation. In the lungs and, possibly, in other organs, under the influence of the virus, local damage to the vascular endothelium occurs, which leads to angiopathy, activation and aggregation of platelets with the formation of blood clots and concomitant consumption of platelets. Systemic hypercoagulation and hyperfibrinogenemia significantly increase the likelihood of large vessel thrombosis and thromboembolic complications, which are detected in 20–30% of patients in the intensive care units. Along with an increase in the level of cytokines in the blood, their content also increases in the lungs and in the bronchoalveolar lavage fluid. Cytokine storm leads to systemic intravascular coagulation, multiple organ failure and death. The review also provides the rationale for the principles of managing patients with coagulopathy based on the known mechanisms of unique disorders inherent in COVID-19. It has been shown that the problem of the pathogenesis of the development of blood clotting disorders in COVID-19 infection remains relevant.